Effects of Borided Cylinder Liner on Engine Performance in a Firing Diesel Engine - Cakir, Mehmet; Akcay, Ismail Hakki (SPRINGER HEIDELBERG, 2015)
The correlations between engine performance and the borided cylinder liner have been investigated experimentally on firing diesel engine. The inner surface of cast iron cylinder liners of the engine was boronized using powder box-boronizing technique at 780 A degrees C for 4 h. The boronizing thickness was approximately 25 mu m at the cross section of cast iron cylinder liner after boronizing process. Diesel engine was operated with original cylinder liner and borided cylinder liner. Engine performance data were measured with the help of a hydraulic dynamometer. Indicated mean effective pressure was measured through the in-cylinder pressure detector. Indicated and brake parameters were compared for both motors. Borided engine liner temperature was measured as higher than that of original engine. Similar measurements were seen in the exhaust temperatures. Mechanical efficiency is improved about 6% with cylinder liner boronizing.
Keywords: Piston-cylinder friction; Engine tribology; Boronizing; PISTON-RING; FRICTION; SURFACES; Science & Technology - Other Topics